Understanding knowledge-intensive organisations within knowledge-based economies: biases and challenges. (1st January 2013) - Khadir-Poggi, Yasmina; Keating, Mary
The recent developments in the theory of organisations and theory of knowledge suggest that more holistic and dynamic approaches are timely. More specifically, this paper critically reflects on the existing approaches on knowledge-intensity in organisations and investigates the organisational and methodological foundations on which the current state of related knowledge is established. It also envisages possible implications on concepts such as intellectual capital and knowledge-based economies. Subsequently, this paper discusses the existing approaches to knowledge-intensive organisations and intellectual capital in relation to both the current techno-economic paradigm and the dominant methodological stance adopted in the literature to date. This paper offers a critical perspective on knowledge-intensive organisations questioning the organisational and philosophical foundations on which the current state of knowledge pertaining to this field is established.